Property as a Comprehensive Institution of Modern Muslim Law - ALEYNIKOVА, Anastasia B. (Journal of Advanced Research in Law and Economics; Vol 9 No 7 (2018): JARLE Volume IX Issue 7(37) Winter 2018, 2019)
The relevance of the study is due to the fact that Russia's relations with the Islamic theocratic states are developing more and more, so it is important for Russian investors to understand the specifics of property relations in these countries in order to minimize risks and expand their economic presence. In this context, this article aims to analyze the positive experience of regulating of legal property regime in the Islamic countries. Leading approach to the study of this problem is the descriptive method that has afforded revealing peculiarities of regulation of the concept of property under consideration within Muslim states. The materials of the paper imply the practical significance for the university teachers of the legal specializations.